Aspectos Psicossociais de pacientes portadores de reações hansênicas no Município de Buriticupu, Estado do Maranhão - CARVALHO, Rosely de Brito Pereira (2014)
This paper studied the psychosocial effects in patients who developed leprosy reaction in Buriticupu’s municipality, State of Maranhão, seeking to ascertain how these aspects affect social interrelationships, the daily life, the process of illness and cure of patients, identifying values and beliefs that may be related in the work. This paper is built based on the testimonies of patients, through semi-structured interviews. The participants were 15 patients with leprosy reaction during or after treatment of leprosy in the period from 2004-2012. The research revealed that the trajectory of these patients was a difficult experience that transformed their lives, their social and affective relationships. It was apparent in speeches prejudice and discriminatory practices, configuring itself as stigma legitimation.